Exploring ethical issues associated with using online surveys in educational research - Roberts, Lynne; Allen, Peter (Routledge, 2015)
Online surveys are increasingly used in educational research, yet little attention has focused on ethical issues associated with their use in educational settings. Here, we draw on the broader literature to discuss 5 key ethical issues in the context of educational survey research: dual teacher/researcher roles; informed consent; use of incentives; privacy, anonymity, and confidentiality; and data quality. We illustrate methods of addressing these issues with our experiences conducing online surveys in educational contexts. Moving beyond the procedural ethics approach commonly adopted in quantitative educational research, we recommend adopting a situated/process ethics approach to identify and respond to ethical issues that may arise during the conduct, analysis, and reporting of online survey research. The benefits of online surveying in comparison to traditional survey methods are highlighted, including the potential for online surveys to provide ethically defensible methods of conducting research that would not be feasible in offline education research settings.